Multi-layer coating

The multilayer coating film addresses chipping resistance and design issues by incorporating a base layer with a controlled erosion index, enhancing durability and aesthetic appeal in automotive applications.

JP7621229B2Active Publication Date: 2025-01-24NIPPON PAINT AUTOMOTIVE COATINGS
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021152482
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-02-22
Filing Date
2021-09-17
Publication Date
2025-01-24
Estimated Expiration
2041-09-17

AI Technical Summary

Technical Problem

Existing multilayer coatings lack sufficient chipping resistance and design properties, particularly in automotive applications, with conventional intermediate coatings and chipping primers failing to adequately protect against damage from impacts while maintaining aesthetic appeal.

Method used

A multilayer coating film comprising a base layer with a controlled erosion index, calculated by multiplying the erosion rate by the film thickness, is designed to improve chipping resistance and incorporate glitter pigments for enhanced design properties, eliminating the need for intermediate coating layers.

Benefits of technology

The coating film achieves both improved chipping resistance and decorative effects, ensuring durability and visual appeal by controlling the erosion index to less than 45 μm²/g, thereby reducing the risk of damage and maintaining a glossy appearance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007621229000001
    Figure 0007621229000001
  • Figure 0007621229000002
    Figure 0007621229000002
  • Figure 0007621229000003
    Figure 0007621229000003
Patent Text Reader

Abstract

To provide a multilayer coating film that has at least a clear coating film and a base coating film, and has excellent chipping resistance, and to provide a multilayer coating film, preferably one that further has excellent design properties.SOLUTION: A multilayer coating film of the present invention includes a substrate, a base layer formed on the substrate, and furthermore, a clear layer formed on the base layer. The base layer contains a brilliant pigment, and when an erosion rate of the base layer is measured with the use of a microslurry jet erosion method at such a projection power that the erosion rate for a silicon wafer becomes 0.635 μm / g, the erosion index is 45 μm2 / g or smaller, which is a value obtained by multiplying the erosion rate of the base layer by a film thickness of the base layer.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a multi-layer coating film. [Background technology]

[0002] In coated objects such as automobile bodies, multi-layer coating films are formed to impart corrosion resistance, chipping resistance, design, scratch resistance, etc., and for example, a multi-layer coating film is formed by forming an intermediate coating film, a base coating film, a clear coating film, and, if necessary, a chipping primer layer, etc., on a steel plate that has been subjected to rust prevention treatment such as electrodeposition coating. Chipping is damage such as cracks and peeling that can occur when a small stone or the like hits the painted surface of the outer plate of an automobile. When chipping occurs, water or the like may penetrate through the chipped area, causing rust, etc., on the base material of the outer plate.

[0003] Conventionally, in order to deal with chipping, development of intermediate coating films or multilayer coating films improved from chipping primers has been promoted. As such multilayer coating films, for example, a multilayer coating film having an intermediate coating film formed from a composition containing an acrylic modified chlorinated polyolefin, a styrene-based plastic elastomer having an acid group, an epoxy resin, a blocked polyisocyanate compound, and a pigment, in which the glass transition temperature of the acrylic part of the acrylic modified chlorinated polyolefin is -50 to 0°C, and the solid mass ratio of the acrylic part to the chlorinated polyolefin part is 7:3 to 2:8 has been proposed (Patent Document 1). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2020-094075 A Summary of the Invention [Problem to be solved by the invention]

[0005] An object of the present invention is to provide a multilayer coating film which has at least a clear coating film and a base coating film and has good chipping resistance, and preferably has an object of providing a multilayer coating film which further has good design properties. [Means for solving the problem]

[0006] In order to solve the above problems, the present invention provides the following aspects. [1] A multilayer coating film having a substrate, a base layer formed thereon, and a clear layer formed on the base layer, The base layer contains a glittering pigment, When the erosion rate of the base layer is measured using a micro slurry jet erosion method with a projection force that results in an erosion rate of 0.635 μm / g for a silicon wafer, the erosion index, which is a value obtained by multiplying the erosion rate of the base layer by the film thickness of the base layer, is 45 μm 2 / g or less. [2] The base layer is composed of one or more layers, When the base layer is composed of two or more layers, the nth layer is designated as the nth base layer, The erosion rate of the nth base layer was measured using the micro slurry jet erosion method with a projection force that resulted in an erosion rate of 0.635 μm / g for the silicon wafer. n ' (μm / g), the thickness of the nth base layer is t n (μm), The multilayer coating film according to [1], wherein the erosion index is calculated based on the following formula:

number

[0007] The multilayer coating film of the present invention has good chipping resistance, and preferably also has good design properties. More preferably, even if the coating film does not have an intermediate coating layer, it can achieve both chipping resistance and design properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] The present inventors have carried out various studies focusing on the base coating film in order to improve chipping resistance, which has been conventionally achieved with intermediate coating films and chipping primers. In these studies, they focused on the erosion rate, which can be considered an index of how easily a coating film is scraped off. They found that chipping resistance itself depends not only on how easily the base coating film is scraped off, but also on the film thickness of the base coating film, and that by multiplying the erosion rate by the film thickness of the base coating film, the effect of film thickness on chipping resistance can be eliminated. They set the index (erosion index) obtained by multiplying the erosion rate by the film thickness at 45 μm. 2 It has been found that by making the hardness equal to or less than 1 / g, the chipping resistance is improved.

[0009] Furthermore, the present inventors have determined that in a coating color with so-called high designability, in which high orientation of the brilliant pigment is required, the base coating film is configured to have a first base coating film and a second base coating film, and the erosion index calculated taking into account the film thicknesses of both coating films is 45 μm. 2 / g, the orientation of the glittering pigment is easily maintained, and chipping resistance can be improved while still providing design appeal. This discovery led to the completion of the present invention.

[0010] The multilayer coating film of the present invention comprises a substrate, a base layer formed thereon, and a clear layer further formed on the base layer.

[0011] The substrate may have at least a base layer such as a metal layer, a plastic layer, a foam layer, etc., and an intermediate coat layer may be formed on the base layer side of the substrate.

[0012] Examples of the metal that forms the metal layer include iron, copper, aluminum, tin, zinc, and alloys thereof. The metal layer may be in the form of a plate or a molded product. Specific examples of the molded product include automobile bodies and parts such as passenger cars, trucks, motorcycles, and buses.

[0013] The metal layer (preferably the base layer side of the metal layer) may be previously subjected to a chemical conversion treatment with a phosphate, a zirconium salt, a chromate, etc., and then an electrodeposition coating layer may be formed on the metal layer. Examples of electrodeposition coating compositions that can be used to form the electrodeposition coating layer include cationic electrodeposition coating compositions and anionic electrodeposition coating compositions.

[0014] Examples of the resin forming the plastic layer include polypropylene resin, polycarbonate resin, urethane resin, polyester resin, polystyrene resin, ABS resin, vinyl chloride resin, and polyamide resin. The plastic layer may be in the form of a plate or a molded product. Examples of the molded product include automobile parts such as spoilers, bumpers, mirror covers, grilles, and doorknobs. The plastic layer (preferably the base layer side of the plastic layer) may be coated with a primer.

[0015] The intermediate coating film is formed from an intermediate coating composition containing an intermediate coating film-forming resin, a color pigment, an extender pigment, etc. As the coating film-forming resin, compounds exemplified as the coating film-forming resin (A) used in the base coating composition described below can be used. As the coating film-forming resin used in the intermediate coating composition, a combination of an acrylic resin and / or a polyester resin with an amino resin and / or an isocyanate is preferably used from the viewpoint of various properties of the intermediate coating film.

[0016] Examples of coloring pigments contained in the intermediate coating composition include pigments with no chroma, such as carbon black and titanium dioxide, and pigments with chroma to complement the hue of the base layer, etc. When the intermediate coating composition contains a pigment, the content of the pigment is preferably 0.1 parts by mass or more, preferably 150 parts by mass or less, more preferably 100 parts by mass or less, and even more preferably 50 parts by mass or less, per 100 parts by mass of the resin solid content.

[0017] The thickness of the intermediate coating film is, for example, preferably 3 to 50 μm, and more preferably 5 to 30 μm.

[0018] The substrate is preferably a substrate layer alone or a laminate of a substrate layer and an intermediate coating layer, and the substrate layer may be a metal layer alone, but is preferably a laminate of a metal layer and an electrodeposition coating layer. That is, the substrate is preferably a metal layer alone; a laminate of a metal layer and an electrodeposition coating layer; or a laminate of a metal layer, an electrodeposition coating layer, and an intermediate coating layer.

[0019] The base layer contains a photoluminescent pigment, and when the erosion rate (E') of the base layer is measured using a microslurry erosion method (MSE method) at a projection force that results in an erosion rate of 0.635 μm / g for a silicon wafer, the erosion index, which is a value obtained by multiplying the erosion rate of the base layer obtained by the above method by the film thickness (t) of the base layer, is 45 μm or more. 2 / g or less. Therefore, the multilayer coating film of the present invention can achieve both design and chipping resistance.

[0020] The erosion index is preferably 44 μm 2 / g or less, more preferably 30 μm 2 / g or less, more preferably 20 μm 2 / g or less, for example, 10 μm 2 / g or more, and 15μm 2 / g or more.

[0021] The erosion rate may be, for example, 3.4 μm / g or less, preferably less than 2.89 μm / g, more preferably 2.88 μm / g or less, even more preferably 2.5 μm / g or less, and even more preferably 2 μm / g or less, but is not limited thereto. When the erosion rate is in the above range, the breaking energy of the base layer is large and impact is absorbed moderately, so that chipping resistance can be improved. In addition, the erosion rate may be, for example, preferably 0.1 μm / g or more, more preferably 0.5 μm / g or more, and even more preferably 0.7 μm / g or more, but is not limited thereto. When the erosion rate is in the above range, the elastic modulus of the base layer is moderate, so that chipping resistance can be improved.

[0022] The MSE method is a test method in which an aqueous dispersion of fine particles (e.g., particle diameter 1-10 μm) dispersed in water is mixed and accelerated by compressed air and projected onto the surface of the sample at high speed (e.g., 60-100 m / s) to cause wear. The characteristics of the sample can be evaluated from the erosion marks and their profile shapes caused by the projection of the fine particles. The erosion rate is a value obtained by dividing the erosion depth by the amount of fine particles projected (projection amount), and can be used as an index of sample strength. For example, a high erosion rate indicates a large erosion depth per unit projection amount and abrasion resistance (i.e., low strength), whereas a low erosion rate indicates a small erosion depth per unit projection amount and abrasion resistance (i.e., high strength).

[0023] The erosion rate of the base layer can be calculated, for example, by performing unit projections so that the erosion depth is in the range of 0.1 to 1 μm, and based on the erosion rate obtained for each unit projection, the erosion rate of the base layer can be calculated. The unit projection amount can be set within the range of 0.5 g to 999 g, so that a sufficient resolution can be obtained in view of the film thickness of the layer.

[0024] In the present invention, the erosion depth refers to the depth from the unirradiated area to the irradiated area.

[0025] More specifically, the measurement of the erosion rate can be carried out by projecting an aqueous dispersion containing fine particles at room temperature (25°C) and atmospheric pressure (1013 hPa) with the projection direction being perpendicular to the surface of the multi-layer coating film and the distance (projection distance) from the projection position to the surface of the multi-layer coating film being 4 mm. In the present invention, the fine particles are polygonal alumina having an average particle diameter D50 of 1.2 μm, and the fine particles are contained in the aqueous dispersion at a ratio of 3 mass%. Furthermore, the projection force during projection is a projection force that gives an erosion rate of 0.635 μm / g for the silicon wafer. The projection force can be adjusted by the projection speed and projection pressure.

[0026] The depth from the unprojected portion to the projected portion can be measured by a stylus-type surface profiler.

[0027] The erosion rate is preferably an average value of values ​​obtained by performing measurements three times.

[0028] The number of layers of the base layer may be 1 or 2 or more. The erosion index of the base layer itself, which is a single layer, may be within the above range, or the base layer may have two or more layers, and the entire base layer may have the above erosion index. Also, the erosion rate of the base layer itself, which is a single layer, may be within the above range, or the base layer may have two or more layers, and at least one of them may have the above erosion rate.

[0029] When the base layer has two or more layers, the erosion rate of the entire base layer can be determined as a weighted average of the erosion rates of the respective layers based on their respective film thicknesses.

[0030] For example, when the base layer has two or more layers, the nth layer is defined as the nth base layer (where n is an integer of 2 or more), and the erosion rate of the nth base layer is defined as E n ' (μm / g), the thickness of the second base layer is t nWhen the thickness of the entire base layer is t (μm) and the thickness of the entire base layer is t (μm), the erosion rate E' (μm / g) of the entire base layer can be calculated based on the following formula.

[0031]

number

[0032] And the erosion index (μm 2 / g) is a value obtained by multiplying the erosion rate E' (μm / g) of the entire base layer by the film thickness t (μm) of the entire base layer, and can be calculated based on the following formula.

[0033]

number

[0034] In particular, when the base layer is composed of a first base layer and a second base layer, when the erosion rate of the first base layer is E1', the erosion rate of the second base layer is E2', the film thickness of the first base layer is t1, and the film thickness of the second base layer is t2, the erosion rate E' of the entire base layer can be calculated based on the following formula. E' = (E1' x t1 + E2' x t2) / (t1 + t2)

[0035] And the erosion index (μm 2 The erosion rate E' (μm / g) of the entire base layer can be calculated by multiplying the erosion rate E' (μm / g) by the sum of the thickness t1 (μm) of the first base layer and the thickness t2 (μm) of the second base layer (i.e., the thickness t of the entire base layer) (E' × (t1 + t2)).

[0036] The base layer contains a glittering pigment, and by containing the glittering pigment, design properties (particularly glittering) are exhibited. In addition, the base layer has two or more layers (preferably two layers), and in particular, the base layer contains the glittering pigment in a highly oriented state, and the erosion index of the entire base layer is 45 μm 2 When the base layer has an erosion rate adjusted in relation to the film thickness of each layer so that the erosion rate is 0.01 to 0.15% by weight or less, the orientation of the luster pigment is maintained by the separation of the functions of each layer, and it becomes easier to obtain a multi-layer coating film that is both highly decorative and chipping-resistant. For this reason, it is also preferable to have a base layer that is composed of a base layer that contains a luster pigment and a base layer that does not contain a luster pigment.

[0037] The luster pigment is a pigment that can reflect light and can impart a unique luster to the coating film. Examples of the luster pigment include metals such as aluminum, copper, zinc, iron, nickel, and tin; alloys of the above metals; metal oxides such as aluminum oxide; metal acid salt compounds such as mica (particularly interference mica pigments, white mica pigments, etc.); graphite, etc., and they may be used alone or in combination of two or more kinds.

[0038] From the viewpoint of glittering properties, the average particle size (D50) of the brilliant pigment is preferably from 2 to 50 μm, more preferably from 10 to 35 μm, and the average thickness is preferably from 0.1 to 5 μm.

[0039] The content of the luster pigment in the entire base layer is preferably 0.1 mass% or more, more preferably 0.5 mass% or more, and even more preferably 1 mass% or more, and is preferably 20 mass% or less, more preferably 15 mass% or less, and more preferably 12 mass% or less.

[0040] When the base layer has two or more layers (preferably a first base layer and a second base layer), at least one layer may contain the luster pigment, and all layers (preferably the first base layer and the second base layer) may contain the luster pigment. In this case, the luster pigment content is the value in the entire base layer. The luster pigment content in each layer may be the same or different between layers.

[0041] In addition, when the base layer has two or more layers, in one embodiment, at least one layer contains a luster pigment, and the erosion index of the entire base layer is within the above range (45 μm 2 In another embodiment, at least one layer contains a luster pigment, and the erosion index of the entire base layer is in the above range (45 μm 2 / g or less), and the erosion rates of all layers (preferably the first base layer and the second base layer) are in the above-mentioned range (less than 2.89 μm / g).

[0042] When the base layer has a first base layer and a second base layer, the first base layer and the second base layer are arranged so that the first base layer is located on the substrate side and the second base layer is located on the clear layer side.

[0043] The thickness of the first base layer is, for example, 3 μm or more, preferably 5 μm or more, and, for example, 50 μm or less, preferably 30 μm or less, more preferably 20 μm or less, and further preferably 10 μm or less.

[0044] The second base layer has a thickness of, for example, 0.1 μm or more, preferably 3 μm or more, more preferably 5 μm or more, and for example, 50 μm or less, preferably 30 μm or less, more preferably 20 μm or less.

[0045] The base layer may include other base layers in addition to the first base layer and the second base layer.

[0046] The base layer is preferably a layer in contact with the clear layer described below.

[0047] The base layer can be formed as a cured product (cured coating film) of a base coating composition containing a coating film-forming resin (A) and a pigment (B). The first base layer and the second base layer can be formed using a first base coating composition and a second base coating composition, respectively, and the components and their contents contained in the first base coating composition and the second base coating composition may be the same as those in the base coating composition unless otherwise specified. The first base coating composition and the second base coating composition may be the same or different.

[0048] The coating film-forming resin (A) preferably contains an acrylic resin (A1) and a urethane resin (A2).

[0049] The acrylic resin (A1) is preferably a polymer of a mixture of α,β-ethylenically unsaturated monomers (monomer mixture).

[0050] Examples of the α,β-ethylenically unsaturated monomer include (meth)acrylic acid esters, polymerizable amide compounds, polymerizable aromatic compounds, polymerizable nitriles, α-olefins, vinyl esters, and dienes.

[0051] In this specification, "(meth)acrylic" means "acrylic and / or methacrylic".

[0052] Examples of the (meth)acrylic acid ester include aliphatic (meth)acrylic acid esters such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and lauryl (meth)acrylate; aromatic acrylic acid esters such as phenyl (meth)acrylate; and alicyclic acrylic acid esters such as isobornyl (meth)acrylate, cyclohexyl (meth)acrylate, t-butylcyclohexyl (meth)acrylate, dicyclopentadienyl (meth)acrylate, and dihydrodicyclopentadienyl (meth)acrylate.

[0053] Examples of the polymerizable amide compound include (meth)acrylamide, N-methylol (meth)acrylamide, N-butoxymethyl (meth)acrylamide, N,N-dimethyl (meth)acrylamide, N,N-dibutyl (meth)acrylamide, N,N-dioctyl (meth)acrylamide, N-monobutyl (meth)acrylamide, N-monooctyl (meth)acrylamide, 2,4-dihydroxy-4'-vinylbenzophenone, N-(2-hydroxyethyl)acrylamide, and N-(2-hydroxyethyl)methacrylamide.

[0054] Examples of the polymerizable aromatic compound include styrene, α-methylstyrene, vinyl ketone, t-butylstyrene, parachlorostyrene, and vinylnaphthalene.

[0055] The polymerizable nitrile includes, for example, (meth)acrylonitrile.

[0056] The α-olefin includes ethylene, propylene, and the like.

[0057] Examples of the vinyl ester include vinyl acetate and vinyl propionate.

[0058] Examples of the diene include butadiene and isoprene.

[0059] The content of the units derived from the α,β-ethylenically unsaturated monomer in the acrylic resin (A1) is preferably 50% by mass or more, more preferably 60% by mass or more, and even more preferably 70% by mass or more, and is preferably 99% by mass or less, more preferably 90% by mass or less. More preferably, it is 85% by mass or less.

[0060] The acrylic resin (A1) preferably contains a unit derived from an α,β-ethylenically unsaturated monomer having an acid group, which allows the acrylic resin (A1) to have an acid group, and thus the water dispersibility of the acrylic resin (A1) can be improved.

[0061] Examples of the α,β-ethylenically unsaturated monomer having an acid group include (meth)acrylic acid, acrylic acid dimer, crotonic acid, 2-acryloyloxyethyl phthalic acid, 2-acryloyloxyethyl succinic acid, ω-carboxy-polycaprolactone mono(meth)acrylate, isocrotonic acid, α-hydro-ω-((1-oxo-2-propenyl)oxy)poly(oxy(1-oxo-1,6-hexanediyl)), maleic acid, fumaric acid, itaconic acid, 3-vinylsalicylic acid, 3-vinylacetylsalicylic acid, 2-acryloyloxyethyl acid phosphate, and 2-acrylamido-2-methylpropanesulfonic acid, of which (meth)acrylic acid and acrylic acid dimer are preferred.

[0062] The content of units derived from the α,β-ethylenically unsaturated monomer having an acid group in the acrylic resin (A1) is preferably 0.5 mass% or more, more preferably 1 mass% or more, and even more preferably 2 mass% or more, and is preferably 15 mass% or less, more preferably 12 mass% or less, and even more preferably 10 mass% or less.

[0063] The acrylic resin preferably contains units derived from an α,β-ethylenically unsaturated monomer having a hydroxyl group, which gives the acrylic resin (A1) a hydroxyl group and can improve crosslinking properties in the base coating composition.

[0064] Examples of the α,β-ethylenically unsaturated monomer having a hydroxyl group include hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, allyl alcohol, (meth)acrylic alcohol, and an adduct of hydroxyethyl (meth)acrylate and ε-caprolactone, and among these, hydroxyethyl (meth)acrylate, hydroxybutyl (meth)acrylate, and an adduct of hydroxyethyl (meth)acrylate and ε-caprolactone are preferred.

[0065] The content of units derived from the α,β-ethylenically unsaturated monomer having a hydroxyl group in the acrylic resin (A1) is preferably 1 mass % or more, more preferably 3 mass % or more, even more preferably 5 mass % or more, and is preferably 30 mass % or less, more preferably 20 mass % or less, even more preferably 15 mass % or less.

[0066] The acrylic resin (A1) may contain a unit derived from a crosslinkable monomer. When the acrylic resin (A1) contains a unit derived from a crosslinkable monomer, it becomes easy to control the average particle size of the acrylic resin (A1) (for example, to 100 nm or less).

[0067] The crosslinkable monomer is a compound having two or more radically polymerizable unsaturated groups in one molecule. Examples of the crosslinkable monomer include bifunctional monomers such as divinylbenzene, ethylene glycol di(meth)acrylate, hexanediol di(meth)acrylate, polyethylene glycol di(meth)acrylate, allyl(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanedi(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, and divinylbenzene; triallyl cyanurate, pentaerythritol tri(meth)acrylate, and the like. Examples of the crosslinkable monomer include trifunctional or higher monomers such as trimethylolpropane tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, and dipentaerythritol hexa(meth)acrylate, and more preferably allyl(meth)acrylate, ethylene glycol di(meth)acrylate, and divinylbenzene. One type of the crosslinkable monomer may be used, or two or more types may be used in combination.

[0068] The content of the units derived from the crosslinkable monomer in the acrylic resin (A1) is preferably 0.2% by mass or more, more preferably 0.5% by mass or more, and preferably 20% by mass or less. When the content of the units derived from the crosslinkable monomer is within the above range, it becomes easy to control the particle size of the acrylic resin (A1) (for example, to 100 nm or less).

[0069] The acid value of the acrylic resin (A1) is preferably 3 mgKOH / g or more, more preferably 7 mgKOH / g or more, and is preferably 100 mgKOH / g or less, more preferably 80 mgKOH / g or less.

[0070] The acrylic resin (A1) has a hydroxyl value of preferably 10 mgKOH / g or more, more preferably 20 mgKOH / g or more, and preferably 180 mgKOH / g or less, more preferably 160 mgKOH / g or less.

[0071] The acid value and hydroxyl value of the acrylic resin (A1) can be calculated based on the composition of the monomer mixture.

[0072] From the viewpoint of mechanical properties, the glass transition temperature of the acrylic resin (A1) is preferably −20° C. or higher and preferably 80° C. or lower. The glass transition temperature of the acrylic resin (A1) can be calculated based on the FOX equation, and for each monomer contained in the monomer mixture forming the acrylic resin (A1), the glass transition temperature of its homopolymer can be referenced to values ​​described in Polymer Handbook (4th edition, Wiley-Interscience, 1999), etc.

[0073] The average particle size of the acrylic resin (A1) is preferably 300 nm or less, more preferably 150 nm or less, and even more preferably 100 nm or less, and is, for example, 20 nm or more, preferably 30 nm or more, and even more preferably 40 nm or more. When the average particle size of the acrylic resin (A1) is within the above range, the transparency and light transmittance of the resulting coating film are good. The average particle size of the acrylic resin (A1) can be measured as a volume average value by dynamic light scattering.

[0074] The number average molecular weight of the acrylic resin (A1) is preferably 1,000 or more, more preferably 3,000 or more, and further preferably 6,000 or more, and the upper limit may be, for example, 300,000. When the acrylic resin (A1) contains a unit derived from a crosslinkable monomer, the number average molecular weight may be outside the above range.

[0075] In this specification, the number average molecular weight and the weight average molecular weight can be measured by gel permeation chromatography (GPC) using polystyrene as a standard sample.

[0076] The acrylic resin (A1) is preferably an emulsion.

[0077] The acrylic resin (A1) may be one type of acrylic resin or a mixture of two or more types of acrylic resins. Specifically, the acrylic resin (A1) may contain an acrylic resin (A1-1) present as an emulsion and another acrylic resin (A1-2).

[0078] The average particle size of the emulsion of the acrylic resin (A1-1) is preferably 300 nm or less, and the lower limit may be, for example, 50 nm or more. The average particle size of the emulsion can be measured as a volume average value by a dynamic light scattering method.

[0079] The acid value of the acrylic resin (A1-1) is preferably 3 to 50 mgKOH / g, more preferably 7 to 40 mgKOH / g, and the hydroxyl value of the acrylic resin (A1-1) is preferably 10 to 150 mgKOH / g, more preferably 20 to 100 mgKOH / g.

[0080] The acid value of the acrylic resin (A1-2) is preferably 10 to 100 mgKOH / g, more preferably 20 to 80 mgKOH / g, and the hydroxyl value of the acrylic resin (A1-2) is preferably 20 to 180 mgKOH / g, more preferably 30 to 160 mgKOH / g.

[0081] The content of the acrylic resin (A1-1) in the acrylic resin (A1) is preferably 50 mass% or more, more preferably 70 mass% or more, even more preferably 75 mass% or more, and is 100 mass% or less, preferably 99 mass% or less, more preferably 95 mass% or less, even more preferably 90 mass% or less.

[0082] The content of the acrylic resin (A1-2) in the acrylic resin (A1) is 0 mass% or more, preferably 1 mass% or more, more preferably 5 mass% or more, even more preferably 10 mass% or more, and is preferably 50 mass% or less, more preferably 30 mass% or less, even more preferably 25 mass% or less.

[0083] When the acrylic resin (A1) has an acid group, the acid group may be neutralized with a base. Neutralization with a base improves the dispersion stability of the acrylic resin (A1). In particular, from the viewpoint of dispersion stability, when the acrylic resin (A1) is an emulsion, it is preferable that the acrylic resin is neutralized with a base so that the pH is 5 to 10. Examples of the base include tertiary amines such as dimethanolamine and triethylamine.

[0084] The content of the acrylic resin (A1) in the solid content of the base coating composition is preferably 15% by mass or more, more preferably 20% by mass or more, and preferably 97% by mass or less, more preferably 80% by mass or less, and even more preferably 70% by mass or less. The content of the acrylic resin (A1) in the coating film-forming resin (A) is preferably 15% by mass or more, more preferably 20% by mass or more, and preferably 97% by mass or less, more preferably 80% by mass or less, and even more preferably 60% by mass or less.

[0085] In this specification, the solid content of a composition refers to the portion of the composition excluding the solvent such as the aqueous medium.

[0086] The acrylic resin (A1) can be produced by polymerizing the monomer mixture, and preferably by emulsion polymerization of the monomer mixture. Specifically, the emulsifier is mixed into an aqueous medium, and the monomer mixture and a polymerization initiator are dropped under heating and stirring. The monomer mixture, emulsifier and water may be emulsified in advance and dropped into the aqueous medium. As the aqueous medium, a compound exemplified as the aqueous medium (C) described later can be appropriately used.

[0087] Examples of the polymerization initiator include azo-based oily compounds such as azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile, 2,2'-azobis(2,4-dimethylvaleronitrile); azo-based aqueous compounds such as anionic 4,4'-azobis(4-cyanovaleric acid), 2,2-azobis(N-(2-carboxyethyl)-2-methylpropionamidine, and cationic 2,2'-azobis(2-methylpropionamidine); redox-based oily peroxides such as benzoyl peroxide, parachlorobenzoyl peroxide, lauroyl peroxide, t-butyl perbenzoate; and aqueous peroxides such as potassium persulfate and ammonium persulfate.

[0088] The amount of the polymerization initiator is generally preferably 0.1 to 5 mass %, more preferably 0.2 to 2 mass %, based on 100 parts by mass of the total monomer mixture.

[0089] The emulsifier may be any emulsifier commonly used by those skilled in the art, and is preferably a reactive emulsifier, such as Antox MS-60 (manufactured by Nippon Nyukazai Co., Ltd.), Eleminol JS-2 (manufactured by Sanyo Chemical Industries, Ltd.), Adeka Reasoap NE-20 (manufactured by Asahi Denka Co., Ltd.), and Aqualon HS-10 (manufactured by Daiichi Kogyo Seiyaku Co., Ltd.).

[0090] The polymerization may be carried out in the presence of a chain transfer agent, such as a mercaptan compound such as lauryl mercaptan, or an α-methylstyrene dimer.

[0091] The polymerization temperature is, for example, 30 to 90° C., and when an azo-based initiator is used, it is preferably 60 to 90° C., and when a redox-based initiator is used, it is preferably 30 to 70. The reaction time is, for example, 1 to 8 hours.

[0092] The polymerization reaction may be a single-stage polymerization or a multi-stage polymerization. As a multi-stage polymerization, for example, it can be carried out in two stages. The two-stage polymerization is a polymerization method in which a part of the above α,β-ethylenically unsaturated monomer mixture (monomer mixture 1) is first emulsion polymerized, and the remaining α,β-ethylenically unsaturated monomer mixture (monomer mixture 2) is further added thereto to carry out emulsion polymerization.

[0093] For example, when two-stage polymerization is performed, it is preferable that the monomer mixture 1 contains an α,β-ethylenically unsaturated monomer having an amide group from the viewpoint of preventing compatibility with the clear coating film. In this case, it is even more preferable that the monomer mixture 2 does not contain an α,β-ethylenically unsaturated monomer having an amide group. Since the monomer mixture 1 and 2 are combined to form the above-mentioned monomer mixture, the requirements for the above-mentioned α,β-ethylenically unsaturated monomer mixture shown above are satisfied by the combination of the monomer mixture 1 and 2.

[0094] The base coating composition contains a urethane resin (A2), which increases the breaking energy of the base layer and makes it easier to absorb impact.

[0095] The urethane resin (A2) is preferably a reaction product of a polyol and a polyisocyanate, and may be a reaction product obtained by further reacting the reaction product of a polyol and a polyisocyanate with a chain extender and / or a terminal terminator.

[0096] Examples of the polyol include polymer polyols, low molecular weight polyols (for example, polyols having a molecular weight of less than 500), and polyols having a hydrophilic group. These may be used alone or in combination of two or more kinds.

[0097] Examples of the polymer polyol include polyether polyol, polyester polyol, polycarbonate polyol, polybutadiene polyol, and polythioether polyol, with polyether polyol being preferred.

[0098] Examples of the polyether polyol include polyethylene glycol, polypropylene glycol, and polytetramethylene glycol.

[0099] Examples of the polyester polyol include a reaction product of a polycarboxylic acid and a polyester raw material polyol, a ring-opening polymer of ε-caprolactone, and copolymers thereof. Examples of the polycarboxylic acid include adipic acid, sebacic acid, itaconic acid, maleic anhydride, phthalic acid, isophthalic acid, and the like, and examples of the polyester raw material polyol include ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, tripropylene glycol, butylene glycol, neopentyl glycol, and the like.

[0100] The weight average molecular weight of the polymer polyol is, for example, 500 or more, preferably 700 or more, more preferably 1,000 or more, and is, for example, 10,000 or less, preferably 7,000 or less. The number of functional groups of the polymer polyol (the number of hydroxyl groups contained in one molecule) is 2 or more, preferably 4 or less, more preferably 3 or less.

[0101] Examples of the low molecular weight polyol include bifunctional or trifunctional or higher aliphatic diols such as ethylene glycol, propylene glycol, 1,4-butanediol, pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, diethylene glycol, glycerin, and trimethylolpropane.

[0102] The hydrophilic group in the polyol having a hydrophilic group includes an anionic group such as an acid group, a cationic group such as an amino group, and a nonionic group such as a polyoxyalkylene group, and the polyol having an anionic group is preferable. By using a polyol having a hydrophilic group, the water dispersibility of the obtained urethane resin can be improved.

[0103] Examples of the polyol having an anionic group include known compounds (for example, the compounds described in JP-B-42-24192 and JP-B-55-41607), and specific examples thereof include dimethylolalkanoic acids such as dimethylolacetic acid, 2,2-dimethylolpropionic acid, and 2,2-dimethylolbutyric acid.

[0104] As the polyol having a cationic group, known compounds (for example, compounds described in JP-B-43-0-76) can be used.

[0105] As the polyol having a nonionic group, a known compound (for example, the compound described in JP-B-48-41718) can be used. Specifically, a polyol having a polyoxyalkylene unit, an alkyl alcohol alkylene oxide adduct, etc. can be used.

[0106] The polyisocyanate is a compound having two or more isocyanate groups in one molecule, and examples of the polyisocyanate include 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, a mixture of 2,4-tolylene diisocyanate and 2,6-tolylene diisocyanate, diphenylmethane-4,4'-diisocyanate, diphenylmethane-2,4'-diisocyanate, and a mixture of diphenylmethane-4,4'-diisocyanate and diphenylmethane-2,4'-diisocyanate. Mixtures of anates, aromatic polyisocyanates such as naphthalene-1,5-diisocyanate, 3,3'-dimethyl-4,4'-biphenylene diisocyanate, xylylene diisocyanate, diphenylmethylmethane diisocyanate, tetramethylxylylene diisocyanate, 4,4'-dibenzyl diisocyanate, 1,3-phenylene diisocyanate; 1,3-cyclopentane diisocyanate, 1,4-cyclohexane diisocyanate, 1,2-cyclohexane diisocyanate, etc. Alicyclic polyisocyanates such as hydrogenated xylylene diisocyanate, dicyclohexylmethane diisocyanate, isophorone diisocyanate, norbornane diisocyanate, and isopropylidenecyclohexyl-4,4'-diisocyanate; aliphatic polyisocyanates such as tetramethylene diisocyanate, pentamethylene diisocyanate, hexamethylene diisocyanate, and trimethylhexamethylene diisocyanate; lysine ester triisocyanate, triisocyanate, and triisocyanate. triisocyanates such as triphenylmethane triisocyanate, 1,6,11-undecane triisocyanate, 1,8-diisocyanate-4,4'-isocyanate methyloctane, 1,3,6-hexamethylene triisocyanate, and bicycloheptane triisocyanate; and polymers of the aromatic polyisocyanates, alicyclic polyisocyanates, and aliphatic polyisocyanates (e.g., adducts, biuret, isocyanurates, and uretdione).Among these, from the viewpoint of light resistance, aliphatic polyisocyanates, alicyclic polyisocyanates, and polymers of aliphatic polyisocyanates or alicyclic polyisocyanates are preferred.

[0107] The chain extender may be any compound having two or more active hydrogen groups in one molecule, and examples of the chain extender include low molecular weight polyols and polyamines.

[0108] Examples of the low molecular weight polyol as the chain extender include the same compounds as the low molecular weight polyols exemplified as the polyols. Examples of the polyamine include ethylenediamine, hexamethylenediamine, diethylenetriamine, hydrazine, xylylenediamine, isophoronediamine, etc.

[0109] The terminal terminator is preferably a compound having one active hydrogen group in one molecule or a monoisocyanate compound.

[0110] The compound having one active hydrogen group in one molecule may be a monoalcohol or a monoamine. The monoalcohol may be an alkyl alcohol such as methanol, butanol, or octanol; an alkyl alcohol alkylene oxide adduct, or the like. The monoamine may be an alkyl amine such as butylamine or dibutylamine.

[0111] Examples of the monoisocyanate compound include aliphatic monoisocyanates such as methyl isocyanate, ethyl isocyanate, propyl isocyanate, butyl isocyanate, and lauryl isocyanate; alicyclic monoisocyanates such as cyclohexyl isocyanate; and aromatic monoisocyanates such as phenyl isocyanate and tolylene isocyanate.

[0112] The glass transition temperature of the urethane resin (A2) is preferably −50° C. or lower, more preferably −55° C. or lower, and further preferably −58° C. or lower, and is, for example, −100° C. or higher, preferably −90° C. or higher. The glass transition temperature of the urethane resin (A2) can be measured by differential scanning calorimetry.

[0113] The urethane resin (A2) may be dispersed in a part of the aqueous medium (C) described below.

[0114] As the urethane resin (A2), commercially available products such as the NeoRez series (Kusumoto Chemical Industries, Ltd.), the HUX series (ADEKA Corporation), the U-coat series, the Permalin series, and the Euprene series (all from Sanyo Chemical Industries, Ltd.) may be used.

[0115] From the viewpoint of increasing the breaking energy of the base layer and absorbing impact, the content of the urethane resin (A2) in the coating-forming resin (A) is 0 mass% or more, preferably 3 mass% or more, more preferably 5 mass% or more, even more preferably 10 mass% or more, and is preferably 80 mass% or less, more preferably 75 mass% or less.

[0116] The coating resin (A) may further contain a melamine resin (A3). The melamine resin (A3) acts as a curing agent in the coating resin (A). The melamine resin (A3) may be water-soluble or water-insoluble.

[0117] The water tolerance of the melamine resin (A3) is preferably 3.0 or more. The water tolerance is an index for evaluating the degree of hydrophilicity, and a higher water tolerance indicates a higher hydrophilicity.

[0118] The water tolerance can be measured as the amount (mL) of ion-exchanged water dropped when 0.5 g of a sample and 10 mL of acetone are mixed and dispersed in a 100 mL beaker at 25°C, and ion-exchanged water is dropped using a burette until the sample becomes cloudy.

[0119] The melamine resin is preferably an alkyl-etherified melamine, and more preferably a melamine resin substituted with a methoxy group and / or a butoxy group.

[0120] Examples of such melamine resins include those having only a methoxy group, such as Cymel 325, Cymel 327, Cymel 370, and Mycoat 723; those having both a methoxy group and a butoxy group, such as Cymel 202, Cymel 204, Cymel 232, Cymel 235, Cymel 236, Cymel 238, Cymel 254, Cymel 266, and Cymel 267 (all trade names, manufactured by Allnex); and those having only a butoxy group, such as Mycoat 506 (trade name, manufactured by Allnex), U-Van 20N60, and U-Van 20SE (trade names, manufactured by Mitsui Chemicals). These may be used alone, or two or more of them may be used in combination.

[0121] From the viewpoint of increasing the breaking energy of the base layer and absorbing impact, the content of the melamine resin (A3) in the coating film-forming resin (A) is preferably less than 50% by mass, more preferably 35% by mass or less, and even more preferably 25% by mass or less, with the lower limit being 0% by mass. The mass ratio of the melamine resin (A3) to the urethane resin (A2) ((A3) / (A2)) is preferably less than 7, more preferably 5 or less, and even more preferably 3 or less, and is preferably 0.01 or more, more preferably 0.05 or more, and even more preferably 0.07 or more.

[0122] The total content of the acrylic resin (A1), urethane resin (A2) and melamine resin (A3) in the coating film-forming resin (A) is preferably 60 mass% or more, more preferably 70 mass% or more, and even more preferably 80 mass% or more, with the upper limit being 100 mass%.

[0123] The coating film-forming resin (A) may further contain other resins (A4) such as polyester resins, polyether resins, polycarbonate resins, etc., as necessary.

[0124] The polyester resin may be a reaction product of a polycarboxylic acid and a polyol, a ring-opening polymer of a lactone compound such as polycaprolactone, or a copolymer thereof. The polycarboxylic acid may be a hydroxy acid such as adipic acid, sebacic acid, isophthalic acid, or dimethylolpropionic acid, or an anhydride thereof. The polyol may be an aliphatic polyol such as ethylene glycol, butanediol, neopentyl glycol, or trimethylolpropane. The solid acid value of the polyester resin is preferably 20 to 80 mgkOH / g, and the number average molecular weight of the polyester resin is preferably 1,000 to 15,000.

[0125] Examples of the polyether resin include polyether polyols having oxyethylene units having 2 to 6 carbon atoms (preferably 2 to 4 carbon atoms) as repeating units, such as polyethylene glycol, polypropylene glycol, and polytetramethylene glycol, and copolymers thereof may also be used.

[0126] Examples of the polycarbonate resin include a reaction product of a polyhydric alcohol with phosgene, and an ester exchange product of a polyhydric alcohol with a carbonate compound.

[0127] The polyhydric alcohol includes linear dihydric alcohols, branched dihydric alcohols, and trihydric or higher alcohols.

[0128] Examples of the linear dihydric alcohol include 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, 1,9-nonanediol, and 1,10-decanediol.

[0129] Examples of the branched dihydric alcohol include 2-methyl-1,3-propanediol, 3-methyl-1,5-pentanediol, neopentyl glycol, 2,2-diethyl-1,3-propanediol, 2-butyl-2-ethyl-1,3-propanediol, 2-methyl-1,8-octanediol, 2,2,4-trimethyl-1,3-pentanediol, 2-ethyl-1,3-hexanediol, 1,4-cyclohexanedimethanol, and tricyclodecane dimethanol.

[0130] Examples of the trihydric or higher alcohol include glycerin, trimethylolethane, trimethylolpropane, a dimer of trimethylolpropane, and pentaerythritol.

[0131] The weight average molecular weight of the other resins is, for example, 500 to 10,000, preferably 1,000 to 10,000, and more preferably 2,000 to 6,000.

[0132] The content of the other resins in the coating film-forming resin (A) is, for example, 40 mass% or less, preferably 30 mass% or less, more preferably 20 mass% or less, and may be 0 mass% or more, 5 mass% or more, or 10 mass% or more.

[0133] The coating film-forming resin (A) may further contain other curing agents (A5). Examples of the other curing agents (A5) include blocked isocyanate compounds in which a blocking agent having an active hydrogen is added to a polyisocyanate such as trimethylene diisocyanate, hexamethylene diisocyanate, xylylene diisocyanate, isophorone diisocyanate, etc.; epoxy compounds; aziridine compounds; carbodiimide compounds; oxazoline compounds; metal ions, etc.

[0134] The coating film-forming resin (A) can be prepared by mixing the acrylic resin (A1), the urethane resin (A2), and, if necessary, the melamine resin (A3), other resins (A4), and other curing agents (A5).

[0135] In the base coating composition which forms the base layer, the content of the film-forming resin (A) in the solid content of the base coating composition is preferably 55 mass% or more, more preferably 65 mass% or more, even more preferably 70 mass% or more, and is preferably 95 mass% or less, more preferably 85 mass% or less, even more preferably 80 mass% or less.

[0136] The pigment (B) contains the luster pigment (hereinafter, may be referred to as "luster pigment (B1)"), and preferably further contains a color pigment (B2).

[0137] The content of the luster pigment (B1) is preferably 0.1 part by mass or more, more preferably 0.5 part by mass or more, and even more preferably 1 part by mass or more, relative to 100 parts by mass of the coating film-forming resin (A), and is preferably 25 parts by mass or less, more preferably 20 parts by mass or less, and even more preferably 15 parts by mass or less.

[0138] The color pigment (B2) may be an organic pigment, an inorganic pigment, or a mixture thereof.

[0139] Examples of the organic pigment include azo chelate pigments, insoluble azo pigments, condensed azo pigments, diketopyrrolopyrrole pigments, phthalocyanine pigments, indigo pigments, perinone pigments, perylene pigments, dioxane pigments, quinacridone pigments, isoindolinone pigments, and metal complex pigments.

[0140] Examples of the inorganic pigment include yellow lead, yellow iron oxide, red iron oxide, carbon black, and titanium dioxide.

[0141] Among them, the color pigment (B2) is preferably a phthalocyanine pigment, a diketopyrrolopyrrole pigment, a perylene pigment, or red iron oxide. By using these color pigments, a coating film having high saturation, high brightness, and excellent color depth can be formed.

[0142] The content of the color pigment (B2) is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, and even more preferably 1 part by mass or more, relative to 100 parts by mass of the coating film-forming resin (A), and is preferably 15 parts by mass or less, more preferably 10 parts by mass or less, and even more preferably 8 parts by mass or less.

[0143] In the base coating composition, when the base coating composition contains the luster pigment (B1) and the coloring pigment (B2), the mass ratio ((B1) / (B2)) of the luster pigment (B1) and the coloring pigment (B2) is preferably 0.8 or more, more preferably 1 or more, even more preferably 1.2 or more, and is preferably 5 or less, more preferably 3 or less, even more preferably 2 or less.

[0144] The pigment (B) may contain other pigments such as an extender pigment.

[0145] The content of the pigment (B) is preferably 0.2 parts by mass or more, more preferably 1 part by mass or more, even more preferably 2 parts by mass or more, and even more preferably 3 parts by mass or more, per 100 parts by mass of the coating film-forming resin (A), and is preferably 35 parts by mass or less, preferably 25 parts by mass or less, even more preferably 20 parts by mass or less, and even more preferably 15 parts by mass or less.

[0146] The base coating composition preferably further comprises an aqueous medium (C). Examples of the aqueous medium include water, a hydrophilic solvent, and a mixture of water and a hydrophilic solvent, and water or a mixture of water and a hydrophilic solvent is preferred.

[0147] Examples of the hydrophilic solvent include alcohol solvents such as methanol, ethanol, n-propanol, and 2-propanol; ketone solvents such as acetone and methyl ethyl ketone; polyhydric alcohol solvents such as ethylene glycol, diethylene glycol, propylene glycol, polyalkylene glycol, and glycerin; ether solvents such as ethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol mono-n-propyl ether, and ethyl carbitol; and amide solvents such as N-methyl-2-pyrrolidone.

[0148] The content of water in the aqueous medium (C) is preferably 50% by mass or more, more preferably 60% by mass or more, and further preferably 70% by mass or more, with the upper limit being 100% by mass.

[0149] In the base coating composition, the content of the aqueous medium (C) is preferably 40 mass% or more, more preferably 50 mass% or more, even more preferably 55 mass% or more, and is preferably 90 mass% or less, more preferably 80 mass% or less, even more preferably 85 mass% or less.

[0150] The base coating composition may further comprise a pigment dispersant.

[0151] As the pigment dispersant, a resin having a pigment affinity portion and a hydrophilic portion can be used. The pigment affinity moiety and hydrophilic moiety may include, for example, nonionic, cationic, and anionic functional groups depending on the type of pigment, and the pigment dispersant may have two or more of the above functional groups in one molecule. Examples of the nonionic functional groups include hydroxyl groups, amide groups, and polyoxyalkylene groups, and examples of the cationic functional groups include amino groups, imino groups, and hydrazino groups. Examples of the anionic functional groups include carboxyl groups, sulfonic acid groups, and phosphoric acid groups.

[0152] Specific examples of the pigment dispersant include nonionic pigment dispersants and polymeric pigment dispersants.

[0153] Examples of the nonionic pigment dispersants include dispersants having an alkyl chain with 14 or more carbon atoms, preferably 14 to 30, and more preferably 16 to 25. The hydrophilic-lipophilic balance (HLB) of the nonionic pigment dispersants is preferably 16 or more, more preferably 16 to 20, and even more preferably 17 to 19. Examples of the nonionic pigment dispersants include polyoxyethylene stearyl ether, polyoxyethylene oleyl ether, polyoxyethylene 2-octyldodidecyl ether, and modified products thereof (sulfuric acid ester, phosphate ester, maleic acid ester modified products, etc.).

[0154] The polymer pigment dispersant is not particularly limited, but the following may be suitably used. (1) A comb-structured polymeric pigment dispersant having a pigment-affinity group in the main chain and / or in multiple side chains and having multiple side chains that constitute a solvation moiety. (2) A polymeric pigment dispersant having multiple pigment affinity moieties in the main chain, each of which is made up of a pigment affinity group. (3) A linear polymer pigment dispersant having a pigment affinity portion consisting of a pigment affinity group at one end of the main chain.

[0155] The pigment affinity group referred to here means a functional group having a strong adsorption force to the surface of the pigment, and examples thereof include, in organosols, tertiary amino groups, quaternary ammonium groups, heterocyclic groups having a basic nitrogen atom, hydroxyl groups, and carboxyl groups; and, in hydrosols, phenyl groups, lauryl groups, stearyl groups, dodecyl groups, and oleyl groups.

[0156] The comb-structured polymeric pigment dispersant (1) has a structure in which a main chain and / or a plurality of side chains having the pigment affinity group and a plurality of side chains constituting a solvation portion are bonded to the main chain, and these side chains are bonded to the main chain like the teeth of a comb. In this specification, the above structure is referred to as a comb structure. In the comb-structured polymeric pigment dispersant (1), the pigment affinity group is not limited to the end of the side chain, and may be present in a plurality of groups in the middle of the side chain or in the main chain. The solvation portion refers to a structure having affinity to a solvent. The solvation portion is composed of, for example, a water-soluble polymer chain, a lipophilic polymer chain, or the like.

[0157] The comb-structured polymeric pigment dispersant (1) is not particularly limited, and examples thereof include poly(ethyleneimine) or its acid salt having one or more poly(carbonyl-C3-C6-alkyleneoxy) chains, each of which has 3 to 80 carbonyl-C3-C6-alkyleneoxy groups and is bonded to the poly(ethyleneimine) by an amide or salt crosslinking group, as disclosed in JP-A-5-177123; a reaction product of poly(lower alkylene)imine and polyester having free carboxylic acid groups, in which at least two polyester chains are bonded to each poly(lower alkylene)imine chain, as disclosed in JP-A-54-37082; and a pigment dispersant obtained by reacting a high molecular weight epoxy compound having epoxy groups at its terminal with an amine compound and a carboxyl group-containing prepolymer having a number average molecular weight of 300 to 7000, simultaneously or in any order, as disclosed in JP-B-7-24746.

[0158] The number of pigment affinity groups contained in the comb-structure polymer pigment dispersant (1) is preferably 2 or more, more preferably 25 or more, per molecule from the viewpoint of dispersion stability, and is preferably 3,000 or less, more preferably 1,500 or less, from the viewpoint of the viscosity of the base coating composition and the pigment dispersion described below.

[0159] The number of side chains constituting the solvated portion contained in the comb-structured polymer pigment dispersant (1) per molecule is preferably 2 or more, more preferably 5 or more, from the viewpoint of dispersion stability, and is preferably 1,000 or less, more preferably 500 or less, from the viewpoint of the viscosity of the base coating composition or the pigment dispersion described below.

[0160] The number average molecular weight of the comb-structured polymer pigment dispersant (1) is preferably 2,000 or more, more preferably 4,000 or more, from the viewpoint of dispersion stability, and is preferably 1,000,000 or less, more preferably 500,000 or less, from the viewpoint of the viscosity of the base coating composition and the pigment dispersion described later.

[0161] The polymeric pigment dispersant (2) having a plurality of pigment affinity moieties composed of pigment affinity groups in the main chain has a plurality of pigment affinity groups arranged along the main chain, and the pigment affinity groups are, for example, pendant on the main chain. In this specification, the pigment affinity moiety refers to a portion having one or more pigment affinity groups and functioning as an anchor for adsorption to the pigment surface.

[0162] Examples of the polymeric pigment dispersant (2) include a reaction product of a polyisocyanate with a mixture of a monohydroxy compound and a monohydroxymonocarboxylic acid or a monoaminomonocarboxylic acid compound, and a compound having at least one basic ring nitrogen and an isocyanate-reactive group, as disclosed in JP-A-4-210220; a polymer having a main chain made of polyurethane / polyurea with a plurality of tertiary amino groups or groups having a basic cyclic nitrogen atom pendant thereon, as disclosed in JP-A-60-16631, JP-A-2-612, and JP-A-63-241018; a copolymer comprising a steric stabilizing unit having a water-soluble poly(oxyalkylene) chain, a structural unit, and an amino group-containing unit, as disclosed in JP-A-1-279919, in which the amine group-containing monomer unit contains a tertiary amino group or a group of an acid addition salt thereof, or a quaternary ammonium group, and the copolymer has an amount of 0.025 to 0.5 milliequivalents per 1 g of the copolymer. Copolymers containing amino groups; amphiphilic copolymers comprising a main chain made of an addition polymer disclosed in JP-A-6-100642 and a stabilizer unit made of at least one alkoxypolyethylene or polyethylene-copropylene glycol (meth)acrylate having 1 to 4 carbon atoms, and having a mass average molecular weight of 2500 to 20000, in which the main chain contains up to 30% by mass of non-functional structural units and up to 70% by mass in total of stabilizer units and functional units, the functional units being substituted or unsubstituted styrene-containing units, hydroxyl group-containing units and carboxyl group-containing units, and the ratios of hydroxyl groups to carboxyl groups, hydroxyl groups to styrene groups, and hydroxyl groups to propyleneoxy groups or ethyleneoxy groups are 1:0.10 to 26.1; 1:0.28 to 25.0; and 1:0.80 to 66.1, respectively.

[0163] The number of pigment-affinity groups in the polymeric pigment dispersant (2) is preferably 2 or more, more preferably 25 or more, per molecule from the viewpoint of dispersion stability, and is preferably 3,000 or less, more preferably 1,500 or less, from the viewpoint of the viscosity and saturation of the base coating composition and the pigment dispersion described below.

[0164] The number average molecular weight of the polymer pigment dispersant (2) is preferably 2,000 or more, more preferably 4,000 or more, from the viewpoint of dispersion stability, and is preferably 1,000,000 or less, more preferably 500,000 or less, from the viewpoint of the viscosity of the base coating composition and the pigment dispersion described later.

[0165] The linear polymer pigment dispersant (3) having a pigment affinity portion consisting of a pigment affinity group at one end of the main chain has a pigment affinity portion consisting of one or more pigment affinity groups at only one end of the main chain, but has sufficient affinity for the pigment surface.

[0166] The linear polymeric pigment dispersant (3) is not particularly limited, and examples thereof include an AB block type polymer in which one end is basic as disclosed in JP-A-46-7294; an AB block type polymer in which an aromatic carboxylic acid is introduced into the A block as disclosed in U.S. Pat. No. 4,656,226; an AB block type polymer in which one end is a basic functional group as disclosed in U.S. Pat. No. 4,032,698; an AB block type polymer in which one end is an acidic functional group as disclosed in U.S. Pat. No. 4,070,388; and an AB block type polymer in which an aromatic carboxylic acid is introduced into the A block as disclosed in U.S. Pat. No. 4,656,226, which has been disclosed in JP-A-1-204,914, and which has improved weather yellowing resistance.

[0167] The number of pigment affinity groups in the linear polymer pigment dispersant (3) is preferably 2 or more, more preferably 5 or more, per molecule from the viewpoint of dispersion stability, and is preferably 3,000 or less, more preferably 1,500 or less, from the viewpoint of the viscosity of the base coating composition and the pigment dispersion described below.

[0168] The number average molecular weight of the linear polymer pigment dispersant (3) is preferably 1,000 or more, more preferably 2,000 or more, from the viewpoint of dispersion stability, and is preferably 1,000,000 or less, more preferably 500,000 or less, from the viewpoint of the viscosity of the base coating composition and the pigment dispersion described later.

[0169] As the pigment dispersant, from the viewpoint of the transparency of the resulting coating film, the comb-structured polymer pigment dispersant (1) is more preferred.

[0170] As the pigment dispersant, commercially available products can also be used. Examples of such commercially available products include the following.

[0171] Dispex Ultra FA4404, Dispex Ultra FA4416, Dispex Ultra FA4425, Dispex Ultra FA4431, Dispex Ultra FA4437, Dispex Ultra FA4480, Dispex Ultra FA4483, Dispex Ultra PA4550, Dispex Ultra PA4560, Dispex Ultra PX4575, Dispex Ultra PX4585 (manufactured by BASF). TEGO Dispers 650, TEGO Dispers 651, TEGO Dispers 652, TEGO Dispers 655, TEGO Dispers 660C, TEGO Dispers 715W, TEGO Dispers 740W, TEGO Dispers 750W, TEGO Dispers 752W, TEGO Dispers 755W, TEGO Dispers 760W (all manufactured by Evonik). Solsperse 12000S, Solsperse 20000, Solsperse 27000, Solsperse 40000, Solsperse 41090, Solsperse 43000, Solsperse 44000, Solsperse 45000, Solsperse 46000, Solsperse 47000, Solsperse 53095, Solsperse 64000, Solsperse 65000, Solsperse 66000, Solsperse 67000, Solsperse WV400 (all manufactured by Lubrizol). Floren G-700AMP, Floren G-700DMEA, Floren GW-1500, Floren GW-1640 (all manufactured by Kyoeisha Chemical Co., Ltd.). Disparlon DA-703-50, Disparlon DA-7301, Disparlon DN-900 (all manufactured by Kusumoto Chemicals). ANTI-TERRA-250, DISPERBYK, DISPERBYK-102, DISPERBYK-180, DISPERBYK-184, DISPERBYK-185, DISPERBYK-187, DISPERBYK-190, DISPERBYK- 191, DISPERBYK-192, DISPERBYK-193, DISPERBYK-194N, DISPERBYK-198, DISPERBYK-199, DISPERBYK-2010, DISPERBYK-2012, DISPERBYK-2013, DISPERBYK-2015, DISPERBYK-2096 (manufactured by BYK).

[0172] The pigment dispersion may be used alone or in combination of two or more kinds.

[0173] The amount (solid content) of the pigment dispersant is preferably 50 to 300 parts by mass, more preferably 65 to 250 parts by mass, relative to 100 parts by mass of the pigment (B). When the amount of the pigment dispersant is within the above range, good pigment dispersion stability and good coating film properties can be easily obtained.

[0174] The base coating composition may further contain, as necessary, additives used in the coating field, such as a surface conditioner, an antioxidant, an ultraviolet absorber, an antifoaming agent, a viscosity control agent, a surfactant, etc.

[0175] By including the viscosity control agent, it is possible to prevent the coating layers from becoming intimately familiar with each other, and to ensure the ease of coating work. As the viscosity control agent, generally, a thixotropic agent can be used. Specific examples of the viscosity control agent include crosslinked or non-crosslinked resin particles; polyamide-based viscosity control agents such as swollen dispersions of fatty acid amides, amide-based fatty acids, and phosphates of long-chain polyaminoamides; polyethylene-based viscosity control agents such as colloidal swollen dispersions of polyethylene oxide; organic bentonite-based viscosity control agents such as organic acid smectite clay and montmorillonite; inorganic pigments such as aluminum silicate and barium sulfate; and flat pigments that exhibit viscosity depending on the shape of the pigment.

[0176] The base coating composition can be produced by stirring and mixing the film-forming resin (A), pigment (B), aqueous medium (C), and, if necessary, a pigment dispersant and additives.

[0177] Prior to the production of the base coating composition, the film-forming resin (A) may be used in the preparation of the base coating composition as a dispersion in at least a part of the aqueous medium (C). When the film-forming resin (A) is in the form of an emulsion or dispersion, these can be mixed and stirred in sequence to form a dispersion in which the film-forming resin (A) is dispersed in at least a part of the aqueous medium (C).

[0178] In the base coating composition, the solid content is preferably 10% by mass or more, more preferably 15% by mass or more, even more preferably 20% by mass or more, and is preferably 60% by mass or less, more preferably 50% by mass or less, even more preferably 55% by mass or less.

[0179] The pigment (B) may be dispersed together with at least a part of the aqueous medium (C) and a pigment dispersion, and the pigment dispersion may be used for preparing the base coating composition. The pigment dispersion may be prepared by mixing and dispersing the pigment (B) and a pigment dispersant in an aqueous medium.

[0180] The color pigment dispersion can be prepared by mixing and dispersing the pigment (B), the aqueous medium (C) and the pigment dispersant.

[0181] The pigment (B), the aqueous medium (C) and the pigment dispersant can be mixed using, for example, a medium disperser, etc. The medium disperser is not particularly limited, but examples thereof include Ultra Apex Mill, Dual Apex Mill (Kotobuki Industries Co., Ltd., product name), Paint Shaker, Picograin Mill, Eco Mill (Asada Iron Works Co., Ltd., product name), Star Mill ZRS, Star Mill, Nano Getter, Max Nano Getter (Ashizawa Finetech Co., Ltd., product name), Micro Media (Buehler Co., Ltd., product name), MSC Mill (Nippon Coke and Engineering Co., Ltd., product name), NPM (Shinmaru Enterprises Co., Ltd.), and Sand Mill.

[0182] As a dispersion medium that can be used in the mixing and dispersion using a medium disperser, for example, a dispersion medium having a particle size of 0.3 mm or less, more preferably 0.1 mm or less, and even more preferably 0.05 mm or less can be used. A dispersion medium having a particle size of 0.05 mm or less is also called an ultrafine medium, and can be particularly suitably used in the preparation of the pigment dispersion (ii) in the present invention. The lower limit of the particle size of the dispersion medium is preferably 0.03 mm, more preferably 0.05 mm, from the viewpoint of the progress of the mixing and dispersion.

[0183] In mixing and dispersing using a media disperser, the amount of media filled in the disperser is preferably 50% by volume, more preferably 60% by volume or more, and even more preferably 70% by volume or more, based on the volume of the disperser.

[0184] The material of the dispersion medium particles is not particularly limited, but examples thereof include alumina, zirconia, silicon carbide, silicon nitride, glass, steel, stainless steel, ceramics, etc. The material of the dispersion medium particles is preferably zirconia in terms of dispersion efficiency, etc.

[0185] The rotation speed of the agitator of the medium dispersing machine is preferably 500 rpm or more, more preferably 1,000 rpm or more, and even more preferably 1,500 rpm or more. The upper limit of the rotation speed is preferably 5,000 rpm or less.

[0186] The medium dispersing machine may have a separator section as necessary. The medium dispersing machine has a separator section, so that the dispersion medium particles can be separated well. The separator section may have, for example, a rotating shaft. The separator section has a rotating shaft, so that the dispersion medium particles can be separated by rotation (for example, centrifugation, etc.). In this case, the rotation speed of the separator rotating shaft can be appropriately selected according to the viscosity of the contents. The rotation speed may be, for example, 2,000 rpm or more, more preferably 3,000 rpm or more, and even more preferably 4,000 rpm or more.

[0187] The mixing and dispersion time by the medium disperser varies depending on the scale, etc., but for example, the residence time in the disperser is preferably 30 to 200 minutes, more preferably 60 to 150 minutes. The mixing and dispersion temperature can be, for example, 5 to 45°C, more preferably 20 to 40°C.

[0188] The solid content in the base coating composition is preferably 10% by mass or more, more preferably 15% by mass or more, even more preferably 20% by mass or more, and is preferably 60% by mass or less, more preferably 50% by mass or less, even more preferably 40% by mass or less.

[0189] The base layer can be formed, for example, by applying the base coating composition to form a coating film, and then heat-curing the coating film. In addition, when the base layer is a multi-layer structure including a first base layer, a second base layer, and the like, the first base coating composition can be applied, the coating film can be heat-cured, and then the second base coating can be applied on the cured first base layer, and the coating film can be heat-cured; the first base coating composition can be applied, and the second base coating composition can be applied without heat-curing the coating film, and the first base coating film and the second base coating film can be cured together. In this case, after applying the first base coating composition, drying or preheating can be performed as necessary before applying the second base coating composition on the coating film.

[0190] Furthermore, the base coating film (the upper coating film in the case of multiple layers) may be heat-cured before forming the layer thereon (clear layer, etc.), or a clear coating composition described below may be applied onto the uncured base coating film (particularly the upper coating film) without heat-curing. In this case, after applying the base coating composition (particularly the upper coating composition), drying or preheating may be performed as necessary before applying the clear coating composition.

[0191] The application of the base coating composition (including multiple layers such as a first base coating composition, a second base coating composition, etc.) can be carried out by multi-stage coating using air electrostatic spray coating, preferably two-stage coating; or by a combination of air electrostatic spray coating and a rotary atomizing type electrostatic coater.

[0192] The clear layer is a layer located on the surface side of the multi-layer coating film relative to the base layer, and is preferably the outermost layer of the multi-layer coating film.

[0193] The resin forming the clear layer is not particularly limited, and examples thereof include acrylic resin, polyester resin, urethane resin, and epoxy resin, and may be cured in combination with a curing agent having an isocyanate group, an epoxy group, or the like (these may be referred to as an "isocyanate curing agent" and an "epoxy curing agent", respectively).

[0194] The thickness of the clear layer is preferably 10 μm or more, more preferably 20 μm or more, from the viewpoint of ensuring the strength of the film itself, and is preferably 80 μm or less, more preferably 60 μm or less, from the viewpoint of suppressing defects such as popping or dripping during painting.

[0195] The clear layer can be formed as a cured product of a clear coating composition containing, for example, a resin such as an acrylic resin, a polyester resin, a urethane resin, or an epoxy resin, and a curing agent having an isocyanate group, an epoxy group, etc. The clear coating composition may be any of a solvent-based, water-based, or powder type.

[0196] Preferred examples of the solvent-based clear coating composition include, from the viewpoints of transparency, acid etching resistance, etc., a combination of an acrylic resin and / or a polyester resin with an amino resin and / or an isocyanate curing agent; or a composition containing an acrylic resin and / or a polyester resin having a carboxylic acid / epoxy curing system and a solvent.

[0197] An example of the water-based clear coating composition is a composition containing a resin used in the solvent-based clear coating composition, which is neutralized with a base such as a tertiary amine (e.g., dimethylethanolamine, triethylamine, etc.) to make it water-based, and an aqueous medium. As the aqueous medium, the compounds exemplified as the aqueous medium (C) used in the base coating composition can be appropriately used.

[0198] The solvent-based clear coating composition and the water-based clear coating composition preferably contain the viscosity control agent in order to ensure ease of coating work.

[0199] Examples of the powder-type clear coating composition include powder coating compositions used in the coating field, such as thermoplastic powder coating compositions, thermosetting powder coating compositions, etc. Among these, thermosetting powder coating compositions such as epoxy-based, acrylic-based and polyester-based compositions are preferred from the viewpoint of coating film properties.

[0200] The clear coating composition can be applied by a coating method that corresponds to the coating form of the clear coating composition used.

[0201] A clear layer can be formed by heat-curing the uncured clear coating film obtained by applying the clear coating composition. When the clear coating composition is applied onto an uncured base layer (particularly the second base layer), both of these uncured coating films are heat-cured by heating. From the viewpoint of curability and physical properties of the resulting multi-layer coating film, the heat-curing temperature is preferably 80 to 180°C, more preferably 120 to 160°C, and the heat-curing time can be set arbitrarily, but for example, when the heat-curing temperature is 120 to 160°C, it is preferably 10 to 30 minutes.

[0202] In forming a multi-layer coating film, the following method can be mentioned as a specific example of a method for forming a first base coating film, a second base coating film, and an optional clear coating film. (1) A method in which a first base coating composition is applied to form an uncured first base coating film, then a second base coating composition is applied to form an uncured second base coating film, and then a clear coating composition is applied to form an uncured clear coating film, and the resulting three layers are heated and cured at the same time. (2) A method in which a first base coating composition is applied to form an uncured first base coating film, then a second base coating composition is applied to form an uncured second base coating film, and the two layers obtained are then heat-cured at the same time. After heat-curing, a clear coating may be provided, if necessary. (3) A first base coating composition is applied to form an uncured first base coating film, and then a clear coating composition is applied to form an uncured clear coating film. The two resulting layers are then cured by heating at the same time. A method in which a second base coating composition is applied to form an uncured second base coating film, then a clear coating composition is applied to form an uncured clear coating film, and the resulting two layers are heat-cured at the same time.

[0203] The multi-layer coating film may further have other layers such as a chipping primer layer in addition to the substrate, base layer, and clear layer. The other layers may be present at any position, such as between the substrate and the base layer, or between the base layer and the clear layer.

[0204] The multilayer coating film has excellent design properties, and preferably has a flip-flop value (hereinafter, sometimes referred to as "FF value") of 1.2 or more. The flip-flop value of the multilayer coating film is preferably 1.4 or more, more preferably 1.5 or more, and may be, for example, 2 or less. The larger the FF value, the higher the flip-flop property.

[0205] In the present invention, "high flip-flop properties" refers to a state in which, when the coating film is visually observed, it is white, sparkling, and has excellent brilliance when viewed from the front (perpendicular to the coating film surface), while when viewed from an oblique direction, it has little brilliance and the hue is clearly visible, and there is a large difference in brightness between the two.

[0206] The thickness of the multilayer coating film is preferably 20 μm or more, more preferably 30 μm or more, from the viewpoint of ensuring the strength of the film itself, and is preferably 300 μm or less, more preferably 250 μm or less, from the viewpoint of maintaining the film properties during thermal cycles and the like.

[0207] The multilayer coating film of the present invention is capable of achieving both design properties and chipping resistance, and can be suitably used for painting automobile bodies and the like. EXAMPLES

[0208] The present invention will be described in more detail with reference to the following examples, but the present invention is not limited thereto.

[0209] Production Example 1: Production of acrylic resin emulsion (film-forming resin) 126.5 parts by mass of deionized water was added to the reaction vessel, and the temperature was raised to 80° C. while mixing and stirring in a nitrogen stream. Next, 100 parts by mass of a monomer mixture of 27.61 parts by mass of methyl acrylate, 53.04 parts by mass of ethyl acrylate, 4.00 parts by mass of styrene, 9.28 parts by mass of 2-hydroxyethyl methacrylate, 3.07 parts by mass of methacrylic acid, and 3.00 parts by mass of allyl methacrylate, 0.7 parts by mass of Aqualon HS-10 (polyoxyethylene alkylpropenyl phenyl ether sulfate, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), 0.5 parts by mass of Adeka Reasoap NE-20 (α-[1-[(allyloxy)methyl]-2-(nonylphenoxy)ethyl]-ω-hydroxyoxyethylene, manufactured by Asahi Denka Co., Ltd.), and 80 parts by mass of a monomer emulsion, 0.3 parts by mass of ammonium persulfate, and an initiator solution consisting of 10 parts by mass of deionized water were dropped into the reaction vessel in parallel over a period of 2 hours. After the dropwise addition, the mixture was aged at the same temperature for 2 hours.Then, the mixture was cooled to 40°C and filtered through a 400 mesh filter, after which 70 parts by mass of deionized water and 0.32 parts by mass of dimethylaminoethanol were added to adjust the pH to 6.5, to obtain a single-layer acrylic resin emulsion 1 having an average particle size of 88 nm, a non-volatile content of 25% by mass, a solid content acid value of 20 mgKOH / g, and a hydroxyl value of 40 mgKOH / g.

[0210] Production Example 2: Production of water-soluble acrylic resin 23.89 parts by mass of tripropylene glycol methyl ether and 16.11 parts by mass of propylene glycol methyl ether were added to the reaction vessel, and the mixture was heated to 105° C. while being mixed and stirred in a nitrogen stream. Next, a monomer mixture containing 13.1 parts by mass of methyl methacrylate, 68.4 parts by mass of ethyl acrylate, 11.6 parts by mass of 2-hydroxyethyl methacrylate, and 6.9 parts by mass of methacrylic acid was prepared, and an initiator solution consisting of 100 parts by mass of the monomer mixture, 10.0 parts by mass of tripropylene glycol methyl ether, and 1 part by mass of tertiary butyl peroxy 2-ethylhexanoate was dropped into the reaction vessel in parallel over 3 hours. After the dropwise addition, the mixture was aged at the same temperature for 0.5 hours.

[0211] Further, an initiator solution consisting of 5.0 parts by mass of tripropylene glycol methyl ether and 0.3 parts by mass of tertiary butyl peroxy 2-ethylhexanoate was added dropwise to the reaction vessel over a period of 0.5 hours. After completion of the addition, the mixture was aged at the same temperature for 2 hours.

[0212] After 16.1 parts by mass of the solvent was distilled off at 110°C under reduced pressure (70 torr) using a solvent remover, 204 parts by mass of deionized water and 7.1 parts by mass of dimethylaminoethanol were added to obtain a water-soluble acrylic resin solution. The non-volatile content of the obtained water-soluble acrylic resin solution was 30% by mass, the solid content acid value was 40 mgKOH / g, the hydroxyl value was 50 mgKOH / g, and the viscosity was 140 poise (E-type viscometer 1 rpm / 25°C).

[0213] Production Example 3 Production of phosphoric acid group-containing organic compound A 1-liter reaction vessel equipped with a stirrer, a temperature regulator, and a cooling tube was charged with 40 parts by mass of ethoxypropanol, and 121.7 parts by mass of a monomer solution consisting of 4 parts by mass of styrene, 35.96 parts by mass of n-butyl acrylate, 18.45 parts by mass of ethylhexyl methacrylate, 13.92 parts by mass of 2-hydroxyethyl methacrylate, 7.67 parts by mass of methacrylic acid, 40 parts by mass of a solution obtained by dissolving 20 parts by mass of Hosmer PP (acid phosphooxyhexa(oxypropylene) monomethacrylate manufactured by Unichemical Co., Ltd.) in 20 parts by mass of ethoxypropanol, and 1.7 parts by mass of azobisisobutyronitrile was added dropwise to the reaction vessel at 120° C. for 3 hours, and stirring was continued for an additional hour. The resulting phosphate group-containing organic compound had an acid value of 105 mgKOH / g, including a phosphate value of 55 mgKOH / g, a hydroxyl value of 60 mgKOH / g, a number average molecular weight of 6,000, and a non-volatile content of 63 mass %.

[0214] Example 1 Manufacture of the first base coating composition (first water-based glossy base coating composition) 182 parts by mass of the acrylic resin emulsion of Production Example 1 as the acrylic resin emulsion (A1-1), 2.2 parts by mass of dimethylaminoethanol as a base, 40 parts by mass of Cymel 327 (mixed alkylated melamine resin, manufactured by Allnex, solid content 90% by mass) as the melamine resin (A3), 10 parts by mass (10 parts by mass per 100 parts by mass of resin solid content) of LG neoExtra White #325 (scale-shaped vapor-deposited metal pigment, manufactured by Oike Kogyo Co., Ltd., average particle size (average major axis) 35 μm, active ingredient 100% by mass) as the brilliant pigment (B1), 5 parts by mass of the phosphate group-containing organic compound of Production Example 3 as a pigment dispersant, 0.4 parts by mass of lauryl acid phosphate, 50 parts by mass of butyl cellosolve as a hydrophilic solvent, and Noigen EA-207D (amphiphilic compound, manufactured by Daiichi Kogyo Seiyaku Co., Ltd., number average molecular weight 4,200, solid content 55% by mass) An aqueous coating composition with a resin solids concentration of 33% by mass was prepared by uniformly dispersing 5.5 parts by mass (3 parts by mass in terms of solids content), 3 parts by mass of linoleic acid (manufactured by Kishida Chemical Co., Ltd.), and 1.0 part by mass of Adekanol UH-814N (urethane association type viscosity agent, active ingredient 30% by mass, manufactured by ADEKA Corporation, product name) as a viscosity adjuster. Dimethylaminoethanol was added to adjust the pH to 8.1, and the composition was diluted with deionized water.

[0215] Preparation of the second base coating composition (second aqueous pigmented base coating composition) The acrylic resin emulsion (A1-1) was 44.9 parts by mass of the acrylic resin emulsion obtained in Production Example 1, 10 parts by mass of a 10% by mass aqueous solution of dimethylaminoethanol as a base, 10.1 parts by mass of the water-soluble acrylic resin of Production Example 2 (resin solid content 30% by mass), 31.2 parts by mass of "Neoletz R-9603" (polycarbonate-based urethane emulsion resin, non-volatile content 33% by mass) manufactured by Avecia as a urethane resin (A2), and melamine resin ( As A3), 8.8 parts by mass of Cymel 204 (mixed alkylated melamine resin manufactured by Allnex, solid content 80% by mass, water tolerance 3.6 ml), 5 parts by mass of Primepol PX-1000 (bifunctional polyether polyol manufactured by Sanyo Chemical Industries) as other resins (A4), 15 parts by mass of cyanine blue (manufactured by Sanyo Dye Co., Ltd.: cyanine blue G-314) as color pigment dispersion (B2), 30 parts by mass of Disperbyk190 as a pigment dispersant, 54.5 parts by mass of ion-exchanged water, and 0.5 parts by mass of BYK-011 as an antifoaming agent were mixed with a stirrer such as a disperser, and then 10.16 parts by mass of the paste obtained by dispersing with a disperser filled with 0.05 mm zirconia beads as a medium at a volume filling rate of 70% was mixed to obtain an aqueous colored base coating composition having PWC 4% by mass relative to 100 parts by mass of resin solids.

[0216] Multi-layer coating production <Multi-layer coating film formation method> A zinc phosphate-treated dull steel plate 0.8 mm thick, 30 cm long and 40 cm wide was electrodeposited with cationic electrodeposition paint "Power Top U-50" (manufactured by Nippon Paint Co., Ltd.) so that the dry film thickness was 20 μm, and the plate was baked at 160°C for 30 minutes. A pre-diluted gray undercoat paint "Orga OP-30" (polyester-melamine paint manufactured by Nippon Paint Co., Ltd.) was applied to the plate using a No. 4 Ford cup so that the discharge time measured at 20°C was 25 seconds, and then the plate was air-sprayed in two stages so that the dry film thickness was 35 μm, and the plate was baked at 140°C for 30 minutes.

[0217] After cooling, the first water-based glitter base paint of the previous manufacturing example was applied in two stages using a Cartridge Bell at room temperature of 23°C and humidity of 68% so that the dry film thickness was 5μm. Between the two applications, an interval of 1 minute 30 seconds was set. After the second application, an interval of 1 minute 30 seconds was set. Then, the plate was preheated at 80°C for 5 minutes to form an uncured first base coating film.

[0218] On the obtained uncured first base coating film, the aqueous colored base coating compositions obtained in the examples and comparative examples were applied in two stages using a "cartridge bell" at room temperature of 23°C and humidity of 68% so that the dry film thickness was 10 μm. Between the two applications, an interval of 1 minute 30 seconds was set. After the second application, an interval of 1 minute 30 seconds was set. Then, preheating was performed at 80°C for 5 minutes to form an uncured second base coating film.

[0219] The resulting coated plate was then cooled to room temperature, and a clear coating of Macflow-O-1810 (a solvent-based clear coating made by Nippon Paint Co., Ltd.) was applied in one stage to a dry film thickness of 35 μm, and the plate was left to set for 7 minutes. The coated plate was then baked in a dryer at 140°C for 30 minutes to obtain a multi-layer coating. The coating appearance was good in both cases.

[0220] Example 2, Comparative Example 1 A multi-layer coating film was formed in the same manner as in Example 1, except that the acrylic resin (A1), the urethane resin (A2), and the melamine resin (A3) in Example 1 were changed as shown in Table 1.

[0221] Examples 3 to 11, Comparative Examples 2 to 4 In Example 1, the acrylic resin (A1), urethane resin (A2), and melamine resin (A3) were changed as shown in Table 1, and a multilayer coating film was formed in the same manner as in Example 1, except that the gray undercoat paint "Orga OP-30" (polyester-melamine paint manufactured by Nippon Paint Co., Ltd.) was not applied.

[0222] The multi-layer coating films obtained in the above Examples and Comparative Examples were subjected to the following measurements.

[0223] [Measurement of erosion rate using the MSE method] At room temperature (25°C) and atmospheric pressure (1013hPa), the direction perpendicular to the surface of the multi-layer coating film was set as the projection direction, and the distance from the projection position to the surface of the multi-layer coating film (projection distance) was set to 4mm. A water dispersion containing 3% by mass of polygonal alumina with an average particle diameter D50 of 1.2μm was projected using a nozzle with an aperture of 1mm. The projection force during projection was set to a projection force that gave an erosion rate of 0.635μm / g for the silicon wafer.

[0224] A unit projection was performed so that the erosion depth was in the range of 0.1 to 1 μm, and the erosion rate of the base layer was measured.

[0225] [Measurement of flip-flop value (FF value)] For the resulting coated test panels, the L* value at an acceptance angle of 15 degrees (L*(15°) value) and the L* value at an acceptance angle of 110 degrees (L*(110°) value) at an incidence angle of 45 degrees were measured using a multi-angle spectrophotometer MA-68II (product name, manufactured by X-Rite Corporation), and the FF value was calculated using the following formula. FF value = L*(15°) value / L*(110°) value

[0226] The deviation of the obtained measured FF value from the target FF value ((measured FF value-target FF value) / target FF value) was used to evaluate the flip-flop property based on the following criteria: The target FF value is an index empirically derived based on the type and amount of the effective pigment, the thickness and number of the base layer, etc., and the closer the deviation value is to 0, the better the flip-flop property is. ○: Within ±10% ×: More than ±10%

[0227] [Chipping resistance measurement] The test plates having the multilayer coating film obtained in each of the Examples and Comparative Examples were subjected to a stone chipping test using a Gravello tester KSS-1 (manufactured by Suga Test Instruments, diamond shot type) under the following conditions. <Test conditions> Stone size: 6~8mm Stone quantity: 0.7~0.8g / piece Distance: 35cm Shot pressure: 0.6kg / cm 2 Shot angle: 15° Test temperature: -20℃

[0228] The area of ​​the coating film peeled off due to the collision was measured using an image processor, and the average value (average value of 10 samples for each) was calculated. The chipping resistance was evaluated according to the following three-level scale. ◎(Excellent): Peeling area 2mm 2 less than ○(Good): Peeling area 2mm 2 More than 2.5mm 2 less than △(Fail): Peeling area 2.5mm 2 End

[0229] [Table 1A]

[0230] [Table 1B]

[0231] [Table 1C]

[0232] The above Examples 1 to 11 are examples of the present invention, and it was confirmed that the obtained multilayer coating film had good chipping resistance. Also, it was confirmed that Examples 1 to 10 had good design properties.

[0233] Comparative Examples 1 to 4 are examples in which the erosion index of the base layer was high, and the chipping resistance was not fully satisfactory. [Industrial Applicability]

[0234] The multilayer coating film of the present invention has good chipping resistance and preferably also has good design properties, and can be suitably used for painting automobile bodies and the like.

Claims

1. A multi-layer coating film having a substrate, a base layer formed thereon, and a clear layer further formed on the base layer, The base layer contains a glittering pigment, When the erosion rate of the base layer was measured using a micro slurry jet erosion method with a projection force that resulted in an erosion rate of 0.635 μm / g for a silicon wafer, the erosion index, which is a value obtained by multiplying the erosion rate of the base layer by the film thickness of the base layer, was 45 μm 2 / g or less.

2. The base layer is composed of one or more layers, When the base layer is composed of two or more layers, the nth layer is designated as the nth base layer, The erosion rate of the nth base layer was measured using a micro-slurry jet erosion method with a projection force at which the erosion rate of the silicon wafer was 0.635 μm / g, and was defined as E n ' (μm / g), the thickness of the nth base layer is t n When (μm), The multi-layer coating film according to claim 1 , wherein the erosion index is calculated based on the following formula: [0010] [wherein n represents an integer of 2 or more.]

Citation Information

Patent Citations

  • Method for forming double-layered coating film

    JP2004337670A

  • Coating composition

    JP2020094075A

  • Method for forming multilayer coating film

    WO2015099150A1

  • Aqueous coating composition and method for forming metallic coating film using same

    WO2017217471A1